PKM Strategi Digital Marketing Dalam Pemasaran Produk Daun Kelor Pada Home Industry Glamori Meto - Antonius Andrias Reis Tanesi (Lembaga Pengembangan Kinerja Dosen, 2024)
In the online era, marketing opportunities using digital technology are very profitable, apart from sellers not having to have a shop, sellers also don't have to go anywhere to sell. The objectives of this activity are (1) Organizing guidance and training for marginalized communities to produce commercial products based on appropriate technology and local resources as well as opportunities to gain access to funding for Micro, Small and Medium Enterprises, (2) Increasing the number of applications of science and technology for the community. This activity was carried out in the first three stages of program socialization and forum group discussion (FGD). The service team planned all the needs that would be used in implementing the service. The service team carried out FGD (Forum Group Discussion) and a cooperation MoU. Second Stage Creating Social Media Accounts Workshop and mentoring on IT knowledge. The third stage of evaluation is carried out to correct any deficiencies found during the service. The main goal is to increase understanding of various social media platforms, effective advertising strategies and ad performance measurement. The method is to use the PKM method with questionnaires and outreach. The results show an increase in home industry players' understanding of the benefits of social media in digital marketing. They are starting to realize the potential of the online market without high advertising costs. This socialization has the potential to increase the application of digital marketing in the home industry. It is recommended that home industry players continue to develop digital marketing capabilities and collaborate to share experiences in managing advertising on social media.